The Tension between Cultural Heritage and Individual Freedom: The JiLu Marriage Tradition among the Indigenous Javanese Community in Blembem, Ponorogo - Rifqi, Muhammad Jazil; Zulfa, Alfina Aulia; Alana, M. Alfian; Syakuri, Ahmad Fauzan (IAIN Ponorogo, 2025)
This study investigates the persistence of JiLu, a Javanese customary prohibition against marriage between the first and third-born children of different families, as practised in Blembem Village, Ponorogo. Although JiLu lacks a formal legal or religious foundation, it continues to function as a binding social norm upheld through oral tradition, communal belief systems, and social sanctions. Employing a socio-legal approach, the research integrates qualitative data from in-depth interviews with traditional elders, affected couples, and local stakeholders, alongside a review of relevant literature. Berger and Luckmann’s theory of social construction—comprising the processes of externalization, objectification, and internalization—provides the theoretical framework to analyze how JiLu is maintained and reproduced. The findings reveal that JiLu operates as a symbolic system that regulates social behaviour, particularly in marital decisions, through emotional reinforcement and the fear of spiritual or social consequences. However, the norm’s authority is increasingly questioned by younger generations exposed to formal education, religious reinterpretation, and modern legal rationality. This generational shift highlights a growing tension between the preservation of collective cultural identity and the assertion of personal autonomy. The study demonstrates how customary norms can either adapt or erode when confronted with changing societal values, contributing to broader discussions on the dynamics of tradition, law, and individual rights in contemporary rural Indonesia.